Metabolic bulk volume from FDG PET as an independent predictor of progression-free survival in follicular lymphoma - So, Heejune; Lee, Hyunjong; Hyun, Seung Hyup; Cho, Young Seok; Moon, Seung Hwan; Choi, Joon Young; Lee, Kyung-Han (Frontiers in Oncology, 2023)
Background: Total metabolic tumor volume (TMTV) in 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) predicts patient outcome in follicular lymphoma (FL); however, it requires laborious segmentation of all lesions. We investigated the prognostic value of the metabolic bulk volume (MBV) obtained from the single largest lesion.Methods: Pretreatment FDG PET/computed tomography (CT) scans of 201 patients were analyzed for TMTV and MBV using a 41% maximum standardized uptake value (SUVmax) threshold.Results: During a median follow-up of 3.2 years, 54 events, including 14 deaths, occurred. Optimal cut-offs were 121.1 cm 3 for TMTV and 24.8 cm 3 for MBV. Univariable predictors of progression-free survival (PFS) included a high Follicular Lymphoma International Prognostic Index 2 (FLIPI2) score, TMTV, and MBV. In the multivariable analysis, high TMTV and MBV were independent predictors of worse PFS (P = 0.0015 and 0.033). Furthermore, in a sub-group with FLIP2 scores of 0-2 (n = 132), high MBV could identify patients with worse PFS (P = 0.007).Readily measurable MBV is useful for stratifying risk in FL patients.